Konsep Pendidikan Karakter Menurut Ibnu Miskawaih dan Relevansinya Dengan Dunia Modern - Yan Yan Supriatman (Rahmad : Jurnal Studi Islam dan Ilmu Al-Qur'an, 2023)
This article aims to explain the concept of character according to Ibnu Miskawaih by examining it in the context of the modern world and the current strong current of globalization. In this article, the author uses a qualitative research method with a library research approach. The results of this research provide an illustration of: According to Ibnu Miskawaih, a person must have three main characteristics. And this is closely related to the soul, which has three powers, namely the power of thinking, the power of anger, and the power of desire. The characteristic of wisdom is the main characteristic for a thinking soul that results from knowledge; courage is the main characteristic for an angry soul that is born from introspection; and cheapness is the main characteristic for a soul of desire that is born from 'iffah (maintaining one's honor). Then, if these three main characteristics are in harmony, the fourth main characteristic will emerge, namely fairness. Furthermore, so that the objectives of character education can be fulfilled, parents and teachers of students become good role models and are supported by a good environment, especially one that is conditioned by the authorities, and the current of globalization and modernization must be utilized as something that supports the creation of the goals of character education.